المواجهة الدولية لظاهرة غسيل الأموال - محمود, يوسف; الخلف, محمد; فرحة, كمال محمود (Latakia University Journal - Economic and Legal Sciences Series, 2019)
أصبح عالم اليوم قريةً صغيرةً بسبب زيادة وسرعة وسهولة وتطور وسائل الاتصال الدولي، ونمو التجارة العالمية وثورة الاتصالات، وقد ظهرت نتيجةً لهذا التطور المذهل منظماتٌ إجراميةٌ عبر الوطنية تمارس العديد من الأنشطة غير المشروعة في المخدرات، الدعارة، الاحتيال، الاتجار بالبشر والأعضاء البشرية، وتهريب المهاجرين، الاتجار بالأسلحة والإرهاب وغيرها، محققةً نتيجةً لهذا التوسع الهائل في نشاطها، أرباحاً ضخمةً، ما جعلها تبحث عن وسائل لغسيل الأموال الناتجة عن تلك النشاطات الإجرامية، ونظراً لما تمثله هذه المنظمات من خطرٍ بالغٍ على سيادة الدول، وعلى المجتمع والأفراد، وعلى الاستقرار الداخلي، حيث أصبحت هذه المنظمات وكأنها دولة داخل دولة تهدد الاقتصاد الوطني والمؤسسات المالية، ولامتداد هذا التأثير إلى المجتمع الولي بأسره ؛ فقد قمنا بإعداد هذا البحث في هذا المجال والتركيز خصوصاً على الجهود الدولية المنسقة لمكافحة هذه الظاهرة الخطيرة. The world today has become a small village because of the tremendous accelerations in communication technologies and its revolution around the world. Consequently, the international trading has become easier, and many criminal organizations have appeared committing all sorts of illegal activities like drugs trading, prostitution, fraud, trafficking in human beings and human organs, migrants smuggling, arms trafficking, and terrorism. As a result of such massive expansion of illegal activities, huge profits have been gained, something that required ways to launder the illegally-gained money from those criminal activities. Such organizations strongly affect the States sovereignty, societies, individuals, and the internal safety and stability of each country. In addition, these organizations have become like a state within a state threatening the national economy and financial institutions. Based on the above-mentioned reasons, we have decided to research in this area and focus on the coordinated international efforts to fight this dangerous phenomenon.